2021
DOI: 10.1002/edn3.231
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial eDNA survey outperforms conventional approach for detecting an invasive pest insect within an agricultural ecosystem

Abstract: Recent methodological advances permit surveys for terrestrial insects from the direct collection of environmental DNA (eDNA) deposited on vegetation or other surfaces. However, in contrast to well‐studied aquatic applications, little is known about how detection rates for such terrestrial eDNA‐based surveys compare with conventional survey methods. Lycorma delicatula, the spotted lanternfly, is an emerging invasive insect in eastern North America, and a significant ecological and economic pest of forested and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 59 publications
2
30
0
Order By: Relevance
“…The positive detection rate of the pest and its biological control predators was 2.8–4.5 times higher using eDNA methods than conventional methods (Tables 2 and 3). A similar increase in detection sensitivity has been reported in a previous study detecting invasive spotted lanternflies in vineyards (Allen et al, 2021). Furthermore, the visual inspections in this study were considerably time‐consuming with a total of 58.2 m of eastern hemlock and 234.9 m of western hemlock foliage being visually inspected.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The positive detection rate of the pest and its biological control predators was 2.8–4.5 times higher using eDNA methods than conventional methods (Tables 2 and 3). A similar increase in detection sensitivity has been reported in a previous study detecting invasive spotted lanternflies in vineyards (Allen et al, 2021). Furthermore, the visual inspections in this study were considerably time‐consuming with a total of 58.2 m of eastern hemlock and 234.9 m of western hemlock foliage being visually inspected.…”
Section: Discussionsupporting
confidence: 87%
“…In the case of A. tsugae detection, the eDNA was detected on all 16 trees, while visual inspection detected them on only 6 trees. A similar increase in sensitivity using eDNA detection of another terrestrial insect pest, the spotted lanternfly, has been reported (Allen et al, 2021). Visual inspection methods can be limited spatially and temporally, while eDNA can persist over time and be transported easily through space.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Though terrestrial ecosystems can be seen as the depository of past biodiversity exploited to reconstruct past ecosystems [ 35 ], the modern and historical signals conveyed by the soil can be difficult to disentangle, leading to a higher risk of false positive detection for contemporary species [ 36 , 37 ]. However, one should be mindful that the total soil eDNA usually corresponds to the current material, as proven by the study carried out by Zinger et al (2009), studying seasonal shifts of communities using soil eDNA.…”
Section: Persistence Detectability and Mobility Of Terrestrial Ednamentioning
confidence: 99%
“…
Recently, environmental DNA (eDNA) has been suggested as an alternative to traditional arthropod monitoring [4]. eDNA analysis has revolutionized the field of biomonitoring [5], and various substrates have been shown to contain arthropod eDNA [6]. A particularly promising source is the surface of plant material, on which arthropods deposit eDNA, for example in chew marks or
…”
mentioning
confidence: 99%